Imbalance in T-cell and cytokine profiles in patients with relapsing-remitting multiple sclerosis - Mikulkova, Z; Praksova, P; Stourac, P; Bednarik, J; Michalek, J (Journal of the neurological sciences, 2011)
Multiple sclerosis (MS) is characterized by autoimmune attack leading to demyelination of the white matter in the central nervous system with devastating clinical consequences. Several immune-mediated destruction mechanisms were previously proposed including different T-cell subsets but complex view on immune system function in patients with MS is missing. In the present study, T-lymphocyte populations and pro-inflammatory as well as suppressive cytokine profiles were evaluated in detail in previously untreated patients with relapsing-remitting MS (RRMS). CD4(+) and CD8(+) naïve, central memory (Tcm), effector memory (Tem), terminal effector memory (Ttem), CD4(+) regulatory T-cells (Treg) and CD8(+) T-suppressor cells (Ts) were analysed using flow cytometry, and levels of ten plasma cytokines were determined using fluorescent bead-based immunoassay. We evaluated two groups of RRMS with minor (n=33) and major (n=25) clinical impairment and compared them with healthy controls (n=40) in order to detect any correlation between severity of MS clinical symptoms and immune disturbances. Significant differences were noted in CD4(+)CD45RA(+)CCR7(+) naïve T-cells, CD4(+)CD45RO(+)CCR7(-) and CD8(+)CD45RO(+)CCR7(-) Tem cells, while no differences were recognized in Tcm, Ttem, Treg and Ts cells in RRMS patients. Nine out of ten studied cytokines were disturbed in plasma samples of patients with RRMS. In conclusion, we demonstrate complex immune dysbalances in untreated MS patients.
Keywords: Multiple Sclerosis, Relapsing-Remitting; T-Lymphocytes; stupeň závažnosti nemoci; Immunophenotyping; imunofenotypizace; počet lymfocytů; mladiství; cytokiny; T-lymfocyty; Middle Aged; mužské pohlaví; Adult; Cytokines; Lymphocyte Count; věkové faktory; ženské pohlaví; Humans; Severity of Illness Index; lidé středního věku; relabující-remitující roztroušená skleróza; Age Factors; dospělí; Female; Adolescent; lidé; Male